2003
DOI: 10.7863/jum.2003.22.5.449
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Waveforms and Blood Flow Parameters of the Superior and Inferior Mesenteric Arteries in Patients Having Behçet Disease With and Without Gastrointestinal Symptoms

Abstract: In this study, symptomatic patients with gastrointestinal Behçet disease were associated with a significant increase in mesenteric artery flow that could be evaluated easily on spectral patterns of arteries during Doppler sonography. The Doppler sonographic findings also revealed that intestinal involvement in patients with Behçet disease without gastrointestinal symptoms is not significantly different from that of healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…In healthy individuals, vertebrobasilar insufficiency is evident when the sum of the VF values in both vertebral arteries is less than 200 mL/min 15 . Siğirci et al 7 found statistically significant differences in terms of VF values in both the superior and inferior mesenteric arteries between symptomatic and asymptomatic patient groups and between symptomatic patients and control participants, and they suggested that these differences developed secondarily to the bowel wall inflammatory process in patients with Behçet disease. In our study, we found that the total VF was statistically significantly lower in the patient groups than in control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy individuals, vertebrobasilar insufficiency is evident when the sum of the VF values in both vertebral arteries is less than 200 mL/min 15 . Siğirci et al 7 found statistically significant differences in terms of VF values in both the superior and inferior mesenteric arteries between symptomatic and asymptomatic patient groups and between symptomatic patients and control participants, and they suggested that these differences developed secondarily to the bowel wall inflammatory process in patients with Behçet disease. In our study, we found that the total VF was statistically significantly lower in the patient groups than in control group.…”
Section: Discussionmentioning
confidence: 99%
“…4 Vascular involvement in patients with Behçet disease includes both arteries and veins, and vascular structures of all sizes may be affected. 5 Many studies have been conducted on many arterial systems [6][7][8] ; however, to our knowledge, no study exists regarding the involvement of the vertebral artery in Behçet disease. Neurologic lesions in Behçet disease are most frequently observed in the areas irrigated by the posterior system 9 ; however, given this location, neurologic involvement may originate from the vertebrobasilar system, but there is no study related to this.…”
mentioning
confidence: 99%
“…Some of the variability could be caused by the difficult angle between the SMA and abdominal surface. In the IMA the blood flow is between 80 -130 ml/min and the RI 0.9 [24,26,130].…”
Section: Recommendationsmentioning
confidence: 99%
“…The splanchnic circulatory system accounts for about 25% of cardiac output at rest 3) , and is supplied from three major arteries that branch off from the abdominal aorta: the celiac artery (CA), superior mesenteric artery (SMA), and inferior mesenteric artery (IMA). The CA supplies blood to the stomach, liver, and spleen, and its flow at rest is reported to be 460~1080 ml/min 6,7) ; the SMA supplies the duodenum, jejunum, ileum, ascending colon, transverse colon, and pancreas, and its flow at rest is 220~540 ml/ min 7,8) ; while the IMA supplies the descending colon, sigmoid colon, and upper rectum, and its flow at rest is 80~130 ml/min 9,10) . Blood in these three arteries flows through the liver via the portal vein.…”
Section: Splanchnic Blood-flow Response To Exercisementioning
confidence: 99%